Transcriptomic profile comparison reveals conservation of ionocytes across multiple organs - Carla Pou Casellas; Cayetano Pleguezuelos-Manzano; Maarten B. Rookmaaker; Marianne C. Verhaar; Hans Clevers (Scientific Reports, 2023)
Abstract Single-cell RNA sequencing has recently led to the identification of a flurry of rare, new cell types, such as the CFTR-high ionocytes in the airway epithelium. Ionocytes appear to be specifically responsible for fluid osmolarity and pH regulation. Similar cells exist in multiple other organs and have received various names, including intercalated cell in the kidney, mitochondria-rich cell in the inner ear, clear cell in the epididymis, and ionocyte in the salivary gland. Here, we compare the previously published transcriptomic profile of cells expressing FOXI1, the signature transcription factor expressed in airway ionocytes. Such FOXI1+ cells were found in datasets representing human and/or murine kidney, airway, epididymis, thymus, skin, inner ear, salivary gland, and prostate. This allowed us to assess the similarities between these cells and identify the core transcriptomic signature of this ionocyte ‘family’. Our results demonstrate that, across all these organs, ionocytes maintain the expression of a characteristic set of genes, including FOXI1, KRT7, and ATP6V1B1. We conclude that the ionocyte signature defines a class of closely related cell types across multiple mammalian organs.